Impact of Social Assistance on Labor Market Mobility : The Case of Turkey - Alcan, Deniz (World Bank, Washington, DC, 2016)
This paper assesses the extent to which social assistance programs in Turkey impact the labor market behavior of those who receive benefits. Theoretically, the possible channels through which the receipt of social assistance may disincentivize work are quite clear, even if the substantial literature analyzing these dynamics is somewhat inconclusive. The analysis confirms that even when controlling for the relevant factors, social assistance beneficiaries are significantly more likely than non-beneficiaries to be unemployed or informally employed, and therefore less likely to be formally employed. Furthermore, among the unemployed, the probability of moving into informal employment is found to be significantly larger for beneficiaries than for non-beneficiaries. The paper concludes that there are potential disincentive effects at play in the decision to work, but particularly in whether to work formally or informally. Finally, an interesting and perhaps counterintuitive finding is that beneficiaries who are inactive are less likely to stay inactive in comparison with non-beneficiaries, which suggests that social assistance may be playing an activation role rather than leading to increased dependency. This, coupled with the previous findings, would indicate that disincentives to work, based on current design parameters, may not be the primary concern. Rather, disincentives to formality may be the prevailing channel through which social assistance affects labor market outcomes. More attention to designing programs that are incentive-compatible with formal employment would be a useful next step for public policy in this area.